Sanitation investments in Ghana: An ethnographic investigation of the role of tenure security, land ownership and livelihoods - Y. Awunyo-Akaba; J. Awunyo-Akaba; M. Gyapong; K. Senah; F. Konradsen; T. Rheinländer (BMC Public Health, 2016)
Abstract Background Ghana’s low investment in household sanitation is evident from the low rates of improved sanitation. This study analysed how land ownership, tenancy security and livelihood patterns are related to sanitation investments in three adjacent rural and peri-urban communities in a district close to Accra, Ghana’s capital. Methods Qualitative data was gathered for this comparative ethnographic study over seven months, (June, 2011-January, 2012) using an average of 43 (bi-weekly) participant observation per community and 56 in-depth interviews. Detailed observational data from study communities were triangulated with multiple interview material and contextual knowledge on social structures, history of settlement, land use, livelihoods, and access to and perceptions about sanitation. Results This study shows that the history of settlement and land ownership issues are highly correlated with people’s willingness and ability to invest in household sanitation across all communities. The status of being a stranger i.e. migrant in the area left some populations without rights over the land they occupied and with low incentives to invest in sanitation, while indigenous communities were challenged by the increasing appropriation of their land for commercial enterprises and for governmental development projects. Interview responses suggest that increasing migrant population and the high demand for housing in the face of limited available space has resulted in general unwillingness and inability to establish private sanitation facilities in the communities. The increasing population has also created high demand for cheap accommodation, pushing tenants to accept informal tenancy agreements that provided for poor sanitation facilities. In addition, poor knowledge of tenancy rights leaves tenants in no position to demand sanitation improvements and therefore landlords feel no obligation or motivation to provide and maintain domestic sanitation facilities. Conclusions The study states that poor land rights, the history of settlements, in-migration and insecure tenancy are key components that are associated with local livelihoods and investments in private sanitation in rapidly changing rural and peri-urban communities of Ghana. Sanitation policy makers and programme managers must acknowledge that these profound local, ethnic and economic forces are shaping people’s abilities and motivations for sanitation investments.